Palliative care facilitates the preparedness of caregivers for thoracic cancer patients. (28th September 2022) - Zomerdijk, Nienke; Panozzo, Stacey; Mileshkin, Linda; Yoong, Jaclyn; Nowak, Anna K.; Stockler, Martin R.; Philip, Jennifer
Abstract: Objective: Palliative care improves outcomes for patients with thoracic cancer; however, limited evidence exists for the benefits of this approach for caregivers. This study aimed to advance understanding of the experiences of palliative care described by bereaved caregivers. Methods: Fifteen adult caregivers completed semi‐structured interviews following prior participation in a randomised controlled trial of early referral to palliative care versus discretionary referral to palliative care. Interviews explored caregiver experiences of palliative care delivery. Interview transcripts were thematically analysed. Results: Four related themes about the experiences of palliative care were identified, each of which required sufficient time between palliative care first contact and death: 'relationship building'; 'clear communication and information'; 'access to practical support'; and 'access to psychosocial support'. The core category underpinning these themes was palliative care facilitates caregiver preparedness . Caregivers noted that palliative care played a critical role in preparing them for the future and described a sense of practical and emotional 'relief' associated with the support services made available to them. Conclusion: Our findings emphasise that palliative care can have a positive impact on caregivers' preparedness for providing the care needed by thoracic cancer patients and that this can improve the experiences of both caregivers and patients.